FREKUENSI GANGGUAN PENDENGARAN PADA BERAT BAYI LAHIR RENDAH - , CORNELY WENNO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Low birth weight babies is one of the risk factors for hearing impairment in newborns. Objective: This study was conducted to determine the frequency of hearing impairment in low birth weight infants. Methods: This study is a descriptive study conducted at a hospital in Yogyakarta. The results are presented in the form of numbers (%). In this study the data of patients with low birth weight infants with hearing impairment obtained from the patient's medical record section Installation and the ENT Medical records from January 1 to December 31, 2011. Results: Respondents with bilateral hearing impairment in infants with low birth weight at girls are 16 cases (15.38%) and unilateral 17 cases (16.34%), bilateral hearing impairmentat boys are 14 cases (13.46%) and unilateral 14 cases (13.46 %). Gestational age <37 weeks with bilateral hearing impairment 26 cases (25%), unilateral 28 cases (26.92%), gestational age 37-42 weeks with bilateral hearing impairment 4 cases (3.84%), unilateral 3 cases (2.88%) . The proportion of birth weight on respondents with hearing impairmentdominated birth weight between 1500-2500 grams, bilateral 17 cases(16.34%), unilateral 19 cases (18.26%). Conclusion: The amount of frequency of hearing impairment in low birth weight infants in the RSUP Dr. Sardjito in 2011 are 61 cases(58.6%), which consists of bilateral hearing impairment frequency by 30 cases(28.8%) and unilateral hearing Impairment by 31 cases(29.8%).